Strategies for achieving high‐level and stable production of toxic Streptomyces phospholipase D in Escherichia coli. Issue 4 (17th December 2018) - Xiong, Weide; Zeng, Xianhai; Ho, Shih‐Hsin; Ling, Xueping; Shen, Liang; Yao, Chuanyi; Lu, Yinghua
Abstract: BACKGROUND: Phospholipase D (PLD) has great potential in the pharmaceutical and food industries for manufacturing bioactive phospholipids. Overproduction of PLD in Escherichia coli is difficult due to its high cytotoxicity which causes plasmid instability, short‐term PLD synthesis, cell lysis and PLD leakage. To address this issue, integrated optimization of PLD production in upstream and downstream processing was performed. RESULTS: Effective strategies in upstream processing include the use of plasmids containing the pSC101 par region in recA − E. coli, the use of moderately strong and tightly regulated promoter PBAD, optimization of codon usage and amino acid supplementation, maintaining the best cellular state by supplementing nutrition, and saturation induction at low temperature. Using these strategies, a large amount of PLD (1.2 × 10 5 U L −1, 81.5 mg L −1 ) was obtained in the batch culture and PLD synthesis lasted 9 h. Additionally, cell lysis did not occur –99% of the recombinant PLD remained in the periplasm. Ultimately, the PLD was purified 327‐fold by a four‐step downstream process comprising extraction with 10 mmol L −1 Ethylenediaminetetraacetic acid and 0.05% (w/v) sodium deoxycholate, ammonium sulfate precipitation, anion exchange and Ni 2+ ‐affinity chromatography. CONCLUSION: This study provides the basis for large‐scale production of PLD in E. coli . © 2018 Society of Chemical Industry